Psychometric properties of the Neuropathic Pain Scale (NPS) in a knee osteoarthritis population. Issue 1 (March 2020) - Lape, Emma C.; Selzer, Faith; Davis, Aileen M.; Collins, Jamie E.; Losina, Elena; Katz, Jeffrey N.
Summary: Objective: Symptoms resembling neuropathic pain (neuropathic-like symptoms) are prevalent in osteoarthritis (OA) populations. Scales that measure neuropathic-like symptoms frequently were established in groups with true neuropathic pain conditions and have not been assessed in OA. We assessed the psychometric properties of the Neuropathic Pain Scale (NPS) in subjects with OA undergoing total knee replacement (TKR). Design: In a prospective study of adults undergoing TKR for OA, we assessed baseline distributions, acceptability (completion rate), internal consistency (Cronbach's alpha), responsiveness 12 months post-TKR, and construct validity of the NPS. We performed factor analysis and created subscales from the items loading onto each retained factor. We evaluated subscale properties and calculated the proportion of total scores attributable to each subscale and compared this with the proportion expected if each item contributed equally. Results: Mean baseline NPS score among 263 participants was 42.7 (SD: 15.9). Cronbach's alpha was 0.88. Factor analysis produced two factors: "bothersome" (items: intense/sharp/dull/unpleasant/deep; Cronbach's alpha = 0.87), and "dysesthetic" (items: cold/sensitive/itchy/surface; alpha = 0.77). Bothersome items contributed more to total NPS scores (74%) than would be expected if each item contributed equally (50%). NPS scores correlated moderately with baseline pain and function, and decreased after TKR, with standardized response means (SRMs) of: total NPS: 1.77, Bothersome subscale: 2.03, Dysesthetic subscale: 0.70. Conclusions: The NPS had acceptable completion, internal consistency, and construct validity, but was not optimal for use in OA; Bothersome subscale items disproportionately drive total NPS scores and may fail to discriminate between nociceptive and neuropathic-like symptoms.